Presenting Farmers’ Welfare through the Agricultural Innovation System (AIS): A Case Study of the Harvest Moon CSR Program by PT PLN Indonesia Power UBP Banten 3 Lontar - Ria Indrawan; Farid Setiawan (Global Writing Academica Researching and Publishing, 2025)
This study aims to explore the implementation of the Agricultural Innovation System (AIS) within the HARVEST MOON CSR program of PT PLN Indonesia Power UBP Banten 3 Lontar, as well as its effectiveness in enhancing the welfare of honey pumpkin farmers in Tangerang Regency, particularly in Lontar Village. The research employed a qualitative method with a case study approach. Data collection techniques included interviews, internal CSR documents, and relevant literature sources. Data analysis was conducted using thematic analysis techniques to map the dimensions of AIS implementation. The findings indicate that the implementation of the Agricultural Innovation System (AIS) in the HARVEST MOON CSR program has successfully improved the welfare of honey pumpkin farmers, as evidenced by an increase in harvest productivity of 960 kg/year (2023–2024) and the lifting of four members of Tim Kreatif Desa Lontar out of poverty. The success of the HARVEST MOON program is supported by the integration of three main AIS dimensions: (1) the integration of agricultural technology innovation, including the use of planting media based on FABA waste and seashells, seed fusion methods as a response to the climate crisis, and crop maintenance technologies; (2) institutional strengthening through the issuance of decrees and capacity-building training for the Tim Kreatif Desa Lontar; and (3) synergy among actors (farmers, academics, village government, and the private sector), successfully realized through mechanisms of translation, alignment, and enrollment.